Diversification of Indonesian Export Markets to Non-Traditional Countries - Guntur Riyanto; Widyastutik Widyastutik; Bayu Krisnamurthi; Abdul Kharis Almasyhari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
The Ukraine-Soviet Union war and the Covid-19 pandemic made the world economy experience complex problems. Indonesia was also affected, especially the decline in exports, so it needed to find new trading partners. This study aims to determine the potential diversification of Indonesia's export market to non-traditional countries, namely Turkey, Brazil, Georgia and the Russian Federation as well as 10 economic commodities. The data used in this study is secondary data. This data is obtained through the GTAP database (Global Trade Analysis Project) version 10. In this GTAP database there are input - output data from 121 countries representing 98% of world GDP. The results of this study are Brazil and Turkey can become Indonesia's trading partners, while Georgia and the Russian Federation have little opportunity to establish trade cooperation with Indonesia